Implementing Change: Development of Campus Department Chair Training - Tim Zauche; Barbara Barnet; Susan Hansen (Academic Chairpersons Conference Proceedings, 2015)
People go to conferences every year and become excited about how to implement change within their own little world. But how often do people actually make that change? This presentation will discuss how a team of five department chairs developed a year-long department chair training for a campus after attending the Academic Chairpersons Conference.
Keywords: Chair Training; Change Agent